60 recipes for Apache CloudStack - Goasguen, Sébastien (O'Reilly Media, 2014)
Planning to deploy and maintain a public, private, or hybrid cloud service? This cookbook's handy how-to recipes help you quickly learn and install Apache CloudStack, along with several API clients, API wrappers, data architectures, and configuration management technologies that work as part of CloudStack's ecosystem. You'll learn how to use Vagrant, Ansible, Chef, Fluentd, Libcloud, and several other open source tools that let you build and operate CloudStack better and faster. If you're an experienced programmer, system administrator, or DevOps practitioner familiar with bash, Git, package.
Includes index. - Print version record
Keywords: Apache CloudStack; Cloud computing; Infonuagique; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference